Axillary lymphadenitis due to Mycobacterium avium-intracellulare. - Colley, E. W. (BMJ Group, 1983)
A 5-year-old girl presented with a swelling in the right axilla from which Mycobacterium avium-intracellulare was cultured. The gland was excised and she made an uneventful recovery.